Design of Turbine Aerator with Remote Control and Internet of Things (IoT)-Based Water pH Monitoring - Mohammad Amar Juliyanto; Indah Sulistiyowati; Ahmad Ahfas (Universitas Ahmad Dahlan, 2023)
Water plays a very important role for living things including fish, with good water fish can grow optimally and healthily. The acidic and alkaline content of water and also oxygen greatly affects its growth. Currently, the majority of fish farmers monitor the pH and oxidation process of the pond manually. Therefore, in an aquaculture business, water quality must be monitored by fish farmers. In this research, an internet of things (IoT) based tool will be made that will produce oxygen in the water in tilapia ponds and is equipped with a pH sensor that will read how much pH value is contained in it, then the data can be viewed remotely via a cellphone connected to the internet. The telemetry system of this aerator research uses the NodeMCU ESP8266 microcontroller then the pH sensor reading data can be seen through the cellphone with the Blynk application as well as the aerator control can be easily done from the application. fish farmers can easily monitor the quality of water pH in real-time as well as control the aerator. The results achieved by the aerator can cause the oxidation process (dissolved oxygen) in water from the rotation of the impeller. Testing was carried out on a tilapia pond with a pond diameter of 15m2. The methodology used is quantitative with the results obtained from 10x experiments and comparison of the pH sensor and also the pH meter shows 96% accuracy of the pH sensor 4502C while 4% for the error value. the pH value before the aerator is active is 6 which means acidic. After the aerator is active and the dissolved oxygen process runs the pH value of the water becomes 7-7.5 which means neutral, this value is good for freshwater fish to breed well. from the help of this tool, fish farming farmers can more efficiently monitor water pH and aerator control.